The Influence Of Employee Work Stress And Employee Compensation On Turnover Intention Mediated By Job Satisfaction - Yanto Yanto; Retno Purwani Setyaningrum; Sunita Dasman (UNIVED Press, 2024)
The study aimed to test a research model that states that the effect of Employee Work Stress and Employee Compensation on Turnover Intention is mediated by Job Satisfaction at PT. Monokem Surya Karawang. This study used a quantitative approach. The respondents of this study were employees of PT Monokem Surya Karawang. Sampling in this study was carried out using Probability Sampling, and sampling was carried out using the Simple Random Sampling method. Sample data collection is carried out by distributing questionnaires through Google Forms. The research analysis used is a structural model processed by SMART-PLS 3.0 software. This study shows that Employee Work Stress has a negative and significant effect on Turnover Intention, Employee Work Stress has a positive and significant effect on Job Satisfaction, Employee Work Stress has a negative and insignificant effect on Turnover Intention even though Job Satisfaction has mediated it, Job Satisfaction has a negative and insignificant effect on Turnover Intention, Employee Compensation has a negative and insignificant effect on Turnover Intention, Employee Compensation has a positive and significant effect on Job Satisfaction, Employee Compensation has a negative and insignificant effect on Turnover Intention even though it has been mediated by Job Satisfaction.